2013
DOI: 10.1111/hiv.12069
|View full text |Cite
|
Sign up to set email alerts
|

Routine HIV testing in the emergency department: tough lessons in sustainability

Abstract: ObjectivesRoutine HIV testing in nonspecialist settings has been shown to be acceptable to patients and staff in pilot studies. The question of how to embed routine HIV testing, and make it sustainable, remains to be answered. MethodsWe established a service of routine HIV testing in an emergency department (ED) in London, delivered by ED staff as part of routine clinical care. All patients aged 16 to 65 years were offered an HIV test (latterly the upper age limit was removed). Meetings were held weekly and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 5 publications
0
53
0
Order By: Relevance
“…A high workload, which is the rule rather than the exception in most emergency departments, is considered by physicians to be one of the major obstacles to HIV testing . The involvement of nursing staff in the counselling and testing process, however, can dramatically increase the frequency of testing, as demonstrated in one study performed in an emergency department in London, UK .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high workload, which is the rule rather than the exception in most emergency departments, is considered by physicians to be one of the major obstacles to HIV testing . The involvement of nursing staff in the counselling and testing process, however, can dramatically increase the frequency of testing, as demonstrated in one study performed in an emergency department in London, UK .…”
Section: Discussionmentioning
confidence: 99%
“…Availability of counselling or a pathway to refer discharged patients for outside counselling and testing should be routinely provided in all emergency departments in order to detect HIV infection early . If available, an acute admissions unit could provide timely in‐house testing without the use of extra resources , but a recent UK audit showed inadequate testing even after introduction of simplified guidelines, particularly in patients with shorter hospital stays and in patients not seen by an infectious disease specialist .…”
Section: Discussionmentioning
confidence: 99%
“…Access to testing however seems to vary widely across healthcare settings in Europe: although most countries offer HIV tests in HIV clinics, sexual health clinics, hospitals and antenatal settings, tests are less available through general practitioners, prisons and tuberculosis services [28]. HIV testing has also been found to be feasible in emergency departments, community-based centres and through use of laboratory-based testing of oral fluid, where each have their own benefits and difficulties in implementation [3033, 34•]. A systematic review assessing barriers to testing in Europe found that there are barriers concerning patients, healthcare providers and at the level of institutions, which include perceived low-risk, fear, accessibility, as well as lack of financial and human resources [35].…”
Section: Hiv Care Cascadementioning
confidence: 99%
“…13 Although rapid HIV testing platforms have been used in most EDs 4–10 that have implemented routine testing, non-rapid technology provides an effective and low-cost strategy for testing large volumes of patients. 11 Large volume HIV testing in EDs helps identify a portion of the 14% 12 of people living with HIV/AIDS in the United States who are as yet unaware of their diagnosis.…”
Section: Introductionmentioning
confidence: 99%